Evaluasi Kinerja Guru - Cantika Ananda; Lara Astaghina; Lahtifa Fauziah (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Teacher performance evaluation is a critical component in improving the quality of education. This study aims to analyze various models, methods, and implementations of teacher performance evaluation with a focus on pedagogical competence, professionalism, and the influence of the educational environment. The methodology includes literature reviews and data analysis from various educational journals. The findings indicate that evaluation models such as CIPP, hybrid methods (ROC and SAW), and evaluations based on pedagogical competence significantly contribute to teachers' professional development. Key findings highlight the importance of pedagogical competence, the impact of performance evaluation on student motivation, and the role of the educational environment in supporting teaching success. Recommendations include implementing structured performance evaluations, continuous professional training for teachers, and adopting student-centered learning approaches. This study provides valuable insights for educators and policymakers to sustainably enhance the quality of education..